391 GENDER INFLUENCES ON DIABETES DISEASE MANAGEMENT IN AN IMPOVERISHED PREDOMINANTLY AFRICAN-AMERICAN MISSISSIPPI POPULATION. (1st January 2005) - Bouldin, M. J.; Sumrall, C. D.; Kotsis, V.; Low, A. K.; Ramsey, L. A.
Abstract : Purpose: Mississippi ranks extremely high in measures of health disparities, diabetes, and all diabetes complications and has the worst quality of care measures in diabetes in the country. One third of African-American women over age 54 have diabetes. Given these circumstances, effective and efficient translation of diabetes care is of paramount concern. This study sought to determine if gender influences the quality of metabolic outcomes in an impoverished predominantly African-American Mississippi population. Methods: Retrospective analysis of 289 medical records was performed. Patients were utilized as their own controls. Three or more visits were required for inclusion and the time interval was 12 months. Initial and final values of HbA1c, BMI, LDL, and blood pressure were recorded. Results: 63.7% were women, 36.3% were men. 67.5% were African-American, 30.8% were Caucasian. 34% had no medical insurance, 26% were on Medicaid. Average HbA1c on presentation was very high and higher in women (10.1 v 9.6). HbA1c decreased markedly in both groups (2.1 (p = .000) v 1.7 (p = .000)); however, the end points were not significantly different. The proportion with HbA1c > 9.0 (58.4 v 53.8) was reduced markedly (28.6 v 19.8). There was improvement in all other outcomes. SBP and DBP improved significantly in women (p = .044, p = .045). LDL improved significantly in both groups (p = .033, p = .042). BMI, which was initially higher for women (34.6 v 31.7), increased (0.7, p = .000), but did not change for men. Except for BMI, the differences in each outcome between men and women were not statistically significant. Conclusion: Men and women were similar in their initial parameters except for BMI. Gender did not appear to influence metabolic outcomes in terms of this diabetes management program. However, women did gain weight significantly compared to men. On average, men's weight did not change despite marked improvement in glycemic control. Though no gender difference in metabolic outcomes was detected, the difference in BMI outcomes may imply a difference in gender management for weight in this population. The fact that there was no difference in metabolic outcomes between genders is encouraging for this state beset by health disparities.